Proceedings of 21th International Drying Symposium 2018
DOI: 10.4995/ids2018.2018.7965
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of oven-dried Jerusalem artichoke powder and its applications in phosphate-free emulsified chicken meatballs

Abstract: In this study, we aimed to investigate chemical and technological characteristics of oven-dried Jerusalem artichoke powder (JAP) to be further incorporated into emulsified chicken meatballs (with/without sodium carbonate) as sodium tripolyphosphate (STPP) replacers. The dietary fiber content of JAP was quite high to improve the health profile of the meat system. JAP samples showed equivalent technological quality to industrial inulin in terms of water-holding, oil-binding, emulsification and gelling abilities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…In contrast, Jerusalem artichoke and cauliflower have very low other total carbohydrates compared to wheat flour ( Table 2 ), which positively affects the caloric value of the total soup formula when the JACF mixture replaces wheat flour 5-20%. The effect of mushroom, Jerusalem artichoke , and cauliflower on the chemical composition of the total soup mixtures agrees with Roncero-Ramos et al, Ahmed and Ali; Yaseen et al, and Öztürk and Serdaroğlu [ 5 , 12 , 26 , 27 ] who reported the proximate compositions of the above plants.…”
Section: Resultssupporting
confidence: 87%
“…In contrast, Jerusalem artichoke and cauliflower have very low other total carbohydrates compared to wheat flour ( Table 2 ), which positively affects the caloric value of the total soup formula when the JACF mixture replaces wheat flour 5-20%. The effect of mushroom, Jerusalem artichoke , and cauliflower on the chemical composition of the total soup mixtures agrees with Roncero-Ramos et al, Ahmed and Ali; Yaseen et al, and Öztürk and Serdaroğlu [ 5 , 12 , 26 , 27 ] who reported the proximate compositions of the above plants.…”
Section: Resultssupporting
confidence: 87%